Chain internal/chain end latent crosslinking in thermoset polymer systems - Matloka, Piotr P; Kean, Zachary; Wagener, Kenneth B (Journal of polymer science. Part A, Polymer chemistry, 2010)
The combination of both chain-internal/chain-end latent crosslinking in a single thermoset polymer system is the subject of this study. A series of linear carbosiloxane/hydrocarbon homopolymers were synthesized by metathesis polycondensation, polymers which serve as the soft phase in the target chain-internal/chain-end latent crosslinked materials. These carbosiloxane/hydrocarbon "soft phase" homopolymers exhibited excellent performance parameters, displaying purely amorphous character with glass transition temperatures ranging between -104 °C and -90 °C depending on the run length of siloxane or hydrocarbon methylene units within the carbosiloxane/hydrocarbon monomer. These soft phase monomers were then copolymerized with latent chain-internal crosslinking carbosilane monomers in the presence of latent chain-end crosslinking molecules thereby generating a new class linear copolymers capable of being moisture cured to produce a new class of silicon-based thermoset systems. Mechanical properties of these thermosets, show breaking strengths up to 0.5 MPa and elongations up to 100%. Both elastic and plastic behavior can be observed in such systems, depending upon the molar ratio of carbosiloxane/hydrocarbon co-monomer and the carbosilane co-monomer.